The history of the doctor’s role and its consequences on public health according to the Tradiciones peruanas by Ricardo Palma - Hualpa Baylón, Johanna Marcela (2019)
This article will analyze the traditions «La camisa de Margarita» and «Muerte en vida». It is proposed to emphasize the way a doctor was called in the Republican era and the role he played in society having as a consequence the unreliability of society and the repercussions on public health.